2004
DOI: 10.1007/s00170-003-1905-6
|View full text |Cite
|
Sign up to set email alerts
|

Finite element simulation of the squaring circular tube

Abstract: The squaring tube process is examined by an incremental elasto-plastic finite-element method based on an updated Lagrangian formulation in which a sliding-sticking friction mode is specifically considered. The high nonlinearity of the process due to the geometric changes, the inelastic constitutive behavior, and the deformation-dependent boundary conditions are taken into account in an incremental manner. A static explicit approach to the solution is applied, the tangent stiffness matrix equation is solved wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The maximum value of error was up to 6% that is acceptable for simulation in metal forming processes. 36
Figure 8.Thickness distributions of drawn tubes. (a) Specified path.
…”
Section: Finite Element Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum value of error was up to 6% that is acceptable for simulation in metal forming processes. 36
Figure 8.Thickness distributions of drawn tubes. (a) Specified path.
…”
Section: Finite Element Simulationmentioning
confidence: 99%
“…They found that the most critical location that thinning occurs is in a location between free-support tube wall and a section in contact with the die. Leu and Wu 6 used number of V-shape dies and moved a circular tube across their channel to produce squared section. They used elasto-plastic finite element analysis under plane-strain condition.…”
Section: Introductionmentioning
confidence: 99%
“…Rectangular steel tubes are widely used as structural elements in numerous applications. The advantages of rectangular pipes over circular tubing include the fact that they are easy-to-fit regarding the direction, produce a high torque when twisting, and reduce the weight of structured parts [ 1 ]. Rectangular pipes are usually produced from a welded round tube using a cold drawing trough and a head, which is comprised of idle rolls [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The topic about the occurrence of collapse is seldom investigated for few articles were found. Leu and Wu [11] had ever explored the effects of various parameters on the degree of asymmetry and the occurrence of collapse for squaring circular tube between two V-shape die in single pressing direction.…”
Section: Introductionmentioning
confidence: 99%